ANALISIS PERBEDAAN KINERJA PERANGKAT KELURAHAN DAN PERANGKAT DESA DITINJAU DARI GAYA KEPEMIMPINAN KOMUNIKASI DAN LINGKUNGAN KERJA - Ernawati, Jemmi Bernardi K. & (Universitas Slamet Riyadi, 2010)
ABSTRACT The goal of the research is: 1) to analyze work achievement of between sub district and vilage officers of Tawangmangu in Karanganyar regency viewed by leadership style, communication and work environment; 2) analyze work achievement of sub district officers if sub district officers are better than work achievement of village Tawangmangu viewed from leadership style, communication and work environment. Sample in this research is amount of 60 people who consist of 30 peoples is sub district officers (from 3 sub district) and 30 people is village officers (from 3 villages). Based on the result of analysis is founded that there is no significance difference between work achievement of sub district officers and village officers viewed from leadership style, communication and work environment. Based on analysis result it is founded that work achievement viewed leadership style, communication and work environment showed average result which is better (mean) than village officers. There is still some weaknesses in this research, among of them are: instrument from the variables, namely leadership style, communication, work environment. The officers of sub district officers and village officers may be not yet able to express an urgent things from research variable. Data sources are sub deviation, because the difference of their backgrounds where sub district officers as state officers, while village officers are not state officers, although their function and assignment is similar. Keywords: leadership style, communication and work environment